A new Puccinia on Thymelaea from Turkey - Kirbag, Sevda; Aime, M. Catherine; Kursat, Murat (Mycotaxon Ltd, 2011)
The rust fungus Puccinia salihae sp. nov. is described from Thymelaea aucheri in East Anatolia, Turkey, producing aecia, uredinia, and telia. This is the first report of a rust disease infecting a species of Thymelaea.
Keywords: phytopathogens; Pucciniales; Thymelaeaceae; Uredinales